BiVO4 photocatalysis design and applications to oxygenÂ productionÂ and degradation of organic compounds: a review - Nguyen, T.D. (Springer Science and Business Media Deutschland GmbH, 2020)
Bismuth vanadate, BiVO4, is a visible-light response semiconductor for photocatalysis applications such as organic pollutants degradation, oxygen production and carbon dioxide reduction. However, as a single-phase photocatalyst, BiVO4 efficiency is limited byÂ the unpreferable recombination of the photoexcited electron (eâ) and hole (h+). Thus, strategies have been designed to enhance theÂ photocatalytic efficiency by promoting the separation of electrons and holes. This can be done by controling the morphology and crystallographic facets of BiVO4, and by building pân junction photocatalytic systems with a combination of n-type semiconductors (BiVO4) and p-type semiconductors or a monoclinicâtetragonal heterostructure of BiVO4. In particular, a direct pân junction photocatalytic system with tetragonal zircon-structured BiVO4 (t-z) and monoclinic scheelite-structured BiVO4 (m-s) combination has recently attracted attention. Here we review the synthesis of theÂ monoclinicâtetragonal heterostructured BiVO4 photocatalyst (mât BiVO4) by calcination, hydrothermal, microwave-assisted hydrothermal and solvothermal methods. mât BiVO4 formation and the transmission phase between t-z and m-s are controlled by the calcining temperature, precursor pH, metal doping content, type of solvent, implementation of precursors and reaction conditions. We discuss mât BiVO4 crystal structure, optical characteristics and photocatalytic principles. Successful formation of BiVO4 crystals with a m-s/t-z heterostructure is based on data from X-ray diffraction (XRD), Raman and ultravioletâvisible diffuse reflectance spectroscopy (UVâVis DRS). In the mât BiVO4 heterostructure, a direct pân junction photocatalytic system is established. When this system is exposed to visible light, the electrons in the conduction band of m-s BiVO4, a n-type semiconductor, migrate easily to the conduction band of t-z BiVO4, while the holes on valence band of t-z BiVO4, a p-type semiconductor, move to the valence band of m-s BiVO4 through an internal electric field. As a result, the eâ/h+ charge carriers are spatially separated. Â© 2020, Springer Nature Switzerland AG.